EVALUATION OF LAND AND WATER MANAGEMENT OPTIONS TO ENHANCE PRODUCTIVITY OF RUBBER PLANTATION USING WaNuLCAS MODEL - Andi Nur Cahyo; Mukand Singh Babel; Avishek Datta; Krishna Chandra Prasad; Roberto Clemente (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2016)
This research aimed to determine the best land and water management by arrangement of plant spacing, irrigation, and drainage of rubber plantation in order to improve rubber plantation productivity. This research was done using The WaNuLCAS (Water, Nutrient and Light Capture in Agroforestry System) model to determine the best land and water management under several scenario combinations of two factors. The first factor was rubber plant spacing arrangement system, which consisted of three levels, i.e. single row (3 x 7 m), single row (3 x 6 m) and double row (2 x 6 x 14 m). The second factor was water management treatment, which consisted of four levels, i.e. without irrigation and drainage, irrigation in dry season, drainage in wet season, and irrigation and drainage in dry and wet season respectively. The results showed that drainage treatment could enhance rubber plantation productivity. Moreover, rubber plantations which were using single row (3 x 7 m), single row (3 x 6 m) and double row (2 x 6 x 14 m) had no significant difference on latex production per hectare.